Understanding Acquisition Performance: The Role of Transfer Effects - Finkelstein, Sydney; Haleblian, Jerayr (Organization Science, 2002)
Drawing on work from transfer theory at the individual unit of analysis, this study examines positive and negative transfer effects in organization acquisitions. Data from 96 organizations reveal that, consistent with theories on positive transfer of industry knowledge, similar acquisitions are positively related to acquisition performance. In addition, consistent with theory on negative transfer of past acquisition knowledge, second acquisitions underperform first acquisitions, particularly when first and second targets are from different industries. In combination, these findings suggest that the routines and practices established in prior situations transfer to new situations, and that the effect of such transfer depends on the similarity of industrial environments.